A 3D-transient elastohydrodynamic lubrication hip implant model to compare ultra high molecular weight polyethylene with more compliant polycarbonate polyurethane acetabular cups. (July 2021) - Ford, Audrey; Hua, Zikai; Ferguson, Stephen J.; Pruitt, Lisa A.; Gao, Leiming
Abstract: Wear remains a significant challenge in the design of orthopedic implants such as total hip replacements. Early elastohydrodynamic lubrication modeling has predicted thicker lubrication films in hip replacement designs with compliant polycarbonate polyurethane (PCU) bearing materials compared to stiffer materials like ultra-high molecular weight polyethylene (UHMWPE). The predicted thicker lubrication films suggest improved friction and wear performance. However, when compared to the model predictions, experimental wear studies showed mixed results. The mismatch between the model and experimental results may lie in the simplifying assumptions of the early models such as: steady state conditions, one dimensional rotation and loading, and high viscosities. This study applies a 3D-transient elastohydrodynamic model based on an ISO standard gait cycle to better understand the interaction between material stiffness and film thickness in total hip arthroplasty material couples. Similar to previous, simplified models, we show that the average and central film thickness of PCU ( ∼ 0 . 4 μ m ) is higher than that of UHMWPE ( ∼ 0 . 2 μ m ). However, in the 3D-transient model, the film thickness distribution was largely asymmetric and the minimum film thickness occurred outside of the central axis. Although the overall film thickness of PCU was higher than UHMWPE, the minimum film thickness of PCU was lower than UHMPWE for the majority of the gait cycle. The minimum film thickness of PCU also had a larger range throughout the gait cycle. Both materials were found to be operating between boundary and mixed lubrication regimes. This 3D-transient model reveals a more nuanced interaction between bearing material stiffness and film thickness that supports the mixed results found in experimental wear studies of PCU hip implant designs.